Bentuk Monomorfemis Ekoleksikon Perikanan Dalam Bahasa Melayu Di Desa Kuala Tanjung Kecamatan Sei Suka Kabupaten Batu Bara Sumatera Utara - Nurmila Syaliha Simbolon; Emilda Emilda; Safriandi Safriandi (Jurnal Ilmiah Kanderang Tingang, 2024)
This research examines the fisheries ecolexicon in Malay in Kuala Tanjung Village, Sei Suka District, Batu Bara Regency, North Sumatra. The aim of this research is to describe the form of fisheries ecolexicon units in Malay based on monomorphism in Kuala Tanjung Village, Sei Suka District, Batu Bara Regency, North Sumatra. This type of research uses a descriptive qualitative approach. The data sources for this research are fishermen and books related to the fisheries ecolexicon. This research data collection technique uses the listening and speaking method. The results of the research show that the fisheries ecolexicon in Malay in Kuala Tanjung Village, Sei Suka District, Batu Bara Regency, North Sumatra produces a monomorphemic lexicon consisting of 50 lexicons.